'Fair Quiet, have I found thee here?': The relationship between garden settings and otium–negotium in sixteenth‐century philosophical dialogues. Issue 3 (11th June 2021) - Moncrieff, Ross
Abstract: Whilst the literary form of the Renaissance philosophical dialogue has increasingly received scholarly attention in recent years, dialogic settings have rarely been the specific, concentrated focus of these efforts. This article will thus pay close attention to the settings, namely garden settings, of Thomas More's Utopia, Niccolò Machiavelli's The Art of War and Justus Lipsius' De Constantia . Building on recent scholarship exploring Renaissance gardens, it suggests that the garden settings of these philosophical dialogues were chosen in order to reflect concerns about the relative merits of the contemplative and active life. Reading the garden as being associated with the contemplative life of otium, it compares the different approaches each of the authors take to their respective garden settings, arguing that the differing portrayals of the garden are informed by an author's stance on otium and the active life of negotium . It demonstrates that paying attention to the settings of philosophical dialogues can open up new and interesting ways of interrogating a text, and that the utility of the garden setting for authors concerned with the otium ‐ negotium conflict was that it was both a stable symbol of otium as well as a site of potential ambiguity and contestation.